Development of low glycemic index crackers from water chestnut and barley flour. Issue 4 (13th March 2020) - Hussain, Syed Zameer; Beigh, Mushtaq; Qadri, Tahiya; Ahmad, Imtiyaz; Naseer, Bazila
Abstract : Purpose: The purpose of the present study was to develop low Glycemic Index (GI) crackers from water chestnut flour (WCF) and barley flour (BF). Design/methodology/approach: Five blends were prepared by mixing WCF with BF in the proportion of 100:0, 70:30, 50:50, 30:70 and 0:100, respectively. The baking process as well as ingredients were modified for the production of low GI crackers. Findings: BF incorporation had significant ( p < 0.05) effect on physical characteristics, organoleptic attributes and glycemic response of crackers. The resistant starch content of final product was found to be higher than WCF and BF. The research confirmed that replacement of 30 percent WCF with BF is feasible for development of low GI crackers with desired sensory attributes. The inference drawn from storage studies was that the developed crackers can be stored safely (with an overall acceptability score of greater than three on a 5-point scale) in metallized polyethylene up to 35 days under refrigerated conditions and 28 days under ambient conditions. Research limitations/implications: Although low GI crackers were developed successfully from WCF and BF in the present study. However, detailed storage studies of such crackers can be done in future so as to perform the tests of type-intensity and temporal dominance of sensation. Also, in view of their low GI, these crops need to be evaluated in future for development of other bakery products like bread, cake, muffins, etc. Practical implications: Water chestnut and barley despite having good nutritional profile and low GI are still considered as underutilized crops. In the present study, these crops were explored for development of low GI crackers especially for people suffering from diabetes. The outcome of this study will open up a new window in the baking sector to develop low GI crackers viz-a-viz will add value to these crops which will help to provide remunerative returns to those who are directly or indirectly involved in trade of these underutilized crops. Originality/value: This was the first reported innovative attempt to develop low GI crackers from WCF and BF. For development of crackers having desired sensory characteristics, it was found feasible to blend WCF and BF in the ratio of 70:30.